Peningkatan Kemampuan Menemukan Rumus Perbandingan Pembelajaran Matematika Siswa Kelas V Sekolah Dasar Berbantuan Media Perstupin - Fitri, Yeni (Jurnal Didaktika Pendidikan Dasar, 2020)
The PERSTUPIN media is one of the teaching aids that can help students determine their own formula in solving everyday problems involving a comparison with known values. Learning by using PERSTUPIN media has been proved effective and successful. This can be seen from the results of the process assessment and the students’ exercises individual assessment. The research method used is development research. The results showed that the use of PERSTUPIN media could improve students 'ability to find formulas, improve students' skills and learning outcomes. The Data obtained from the results of the process assessment showed that  20 students (83.33%) got an A and 4 students (16.67%) got a B score. The improvement in the quality of the learning process gave a positive impact on the improvement of the quality of learning achievement. This is based on the average of student assessment, which is 94. Meanwhile, the number of students who got learning completeness above the KKM was 100% (24 students). Based on these data, it can be concluded media PERSTUPIN has been proved effective and successful in improving the students’ ability to find a comparison formula.